A view to a kill [videorecording (Blu-Ray)] - Glen, John, 1932-; Moore, Roger, 1927-2017; Roberts, Tanya, 1955-2021-; Jones, Grace; Macnee, Patrick, 1922-2015; Walken, Christopher, 1943-; Fleming, Ian, 1908-1964 (007., 2015)
James Bond 007 is pitted against two deadly villains, super-intelligent Max Zorin, the product of a Nazi genetic experiment, and his partner May-Day. They are involved in taking over the microchip monopoly.